1997
DOI: 10.1086/516447
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Core Protein Mutations Are Concentrated in B Cell Epitopes in Progressive Disease and in T Helper Cell Epitopes during Clinical Remission

Abstract: The distribution and temporal and clinical features of amino acid substitutions of the core protein of hepatitis B (HB) virus were analyzed, using at least 2 sequential samples from 27 patients. Six patients seroconverted from HBe antigen (HBeAg)-positive to anti-HBe-positive (3 went into remission), and 21 were continuously anti-HBe positive with progressive hepatitis. Precore mutations, which terminate HBeAg translation, all appeared by the second sample. Most core mutations occurred between the first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
6
47
0
1
Order By: Relevance
“…Nucleotide (synonymous) and amino acid (nonsynonymous) substitutions within universally recognized T helper (Th 1 to 20 and Th 50 to 69), CTL (CTL 18 to 27 and CTL 141 to 151), and B-cell (B 74 to 89, B 107 to 118, and B 130 to 138) immunodominant epitopes were compared with wild-type sequences, and the results were expressed as the number of differences in substitutions (6,7,23,25,33).…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide (synonymous) and amino acid (nonsynonymous) substitutions within universally recognized T helper (Th 1 to 20 and Th 50 to 69), CTL (CTL 18 to 27 and CTL 141 to 151), and B-cell (B 74 to 89, B 107 to 118, and B 130 to 138) immunodominant epitopes were compared with wild-type sequences, and the results were expressed as the number of differences in substitutions (6,7,23,25,33).…”
Section: Methodsmentioning
confidence: 99%
“…These data support the notion that HBcAg is a unique B-cell immunogen, although the molecular basis for this has remained unknown. An interesting observation is that during infection, the C gene of HBV often displays genetic deletions within the tip of the protruding spikes of HBcAg, which are known to contain the major site for antibody binding (5,7). These have been referred to as core internal deletion variants, and they often appear in end stage liver disease (5).…”
mentioning
confidence: 99%
“…An interesting observation is that during infection, the C gene of HBV often displays genetic deletions within the tip of the protruding spikes of HBcAg, which are known to contain the major site for antibody binding (5,7). These have been referred to as core internal deletion variants, and they often appear in end stage liver disease (5). Depending on the nature of the deletion, they may still form functional capsids, as determined by electron microscopy (19).…”
mentioning
confidence: 99%
“…It has been shown that this variant exhibits a high prevalence of mutations in the core region [Alexopoulou et al, 1997[Alexopoulou et al, , 1998Carman et al, 1997;Maruyama et al, 2000]. Sequence variation is one of the most powerful viral strategies for escaping recognition by the host's immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence variation is one of the most powerful viral strategies for escaping recognition by the host's immune response. Core heterogeneity has been investigated thoroughly [Alexopoulou et al, 1997[Alexopoulou et al, , 1998Carman et al, 1997;Maruyama et al, 2000;Hadziyannis and Papatheodoridis, 2006] and linked to virus persistence. It was demonstrated previously that a mixed viral population of various quasi-species circulates in the serum at any one time during chronic HBV infection [Alexopoulou et al, 1997].…”
Section: Discussionmentioning
confidence: 99%